The Effect of Alcoholic Beverages on Surface Roughness of Acrylic Denture Base Material - Gladis Aprilla Rizki; Sri Wahyuningsih Rais; Martha Mozartha (SONDE (Sound of Dentistry), 2020)
Alcoholic beverages can be consumed in any group age, and it may be consumed by an individual using denture. Fluid absorption by heat-cured acrylic resin as a material of a denture base was able to cause an increase in its surface roughness. Absorption of an organic solvent such as the ethanol in an alcoholic beverage(s) could even increase the effect. This study aimed to evaluate the effect of alcohol beverages on surface roughness of heat-cured acrylic resin denture base. Samples (n=24) were prepared from heat-cured acrylic resin (25x25x5 mm). They were divided into 4 groups and the pre-test surface roughness was measured. Samples of each group were immersed for 10 minutes into the solution (distilled water as the control group, beer, wine, and whiskey as the test groups). After stored in artificial saliva for 23 hours, the samples were immersed into the solution, completing a period of 24 hours. This procedure was performed for 7 consecutive days and the post-test surface roughness was measured. Data were statistically analyzed using the Kruskal-Walis test. There was a significant difference in surface roughness measurement before and after the immersion (p<0.05). Whiskey was most affecting the surface roughness of heat-cured acrylic resin denture base. Alcoholic beverages could increase the surface roughness of heat cure acrylic resin denture base. Keywords: Alcoholic beverages; Heat-cured acrylic denture base; Surface roughness